PROBLEM DEFINISI GENDER: KAJIAN ATAS KONSEP NATURE DAN NURTURE - Moh. Khuza’i (Universitas Darussalam Gontor, 2013)
There are three things examined in this article, the definition of gender, the concept of nature, and the concept of nurture. These three things need to be studied, because they are the keywords for feminists to spread their ideas to the world of Islam. The existence of feminism should be criticized, as historically this understanding did not make women better in running their lives. That because of problems in the concept of feminism and itsnegative effect. The caution is needed, because the gender activists often point to the backwardness of women and the suppression of them by showing the incorrect reasons. In addressing the differences between men and women, Islam has a better concept than feminism. Islam has a concept of fitrah and amanah. This paper tries to study theconcept of nature and nurture in the Islamic perspective, tries to present an alternative in addressing the differences between men and women, also tries to shows the proof whether Islam leans to the one of two concepts being debated.